ASSA14-10-01 Haemodynamic effects of short-term infusion of recombinant human atrial natriuretic peptide (rhANP) for acute decompensated heart failure: a randomised, double-blind, placebo-controlled, multicenter study. (1st December 2014) - Wang, G; Wang, P; Huang, J; Tan, H; Liu, W; Zhang, J; Liao, Z; Yu, L; Mao, Y; Ye, S; Feng, L; Zhang, Y; et al.
Abstract : Objectives: This study was designed to confirm haemodynamic effects of short-term infusion of recombinant human atrial natriuretic peptide (rhANP) at the prespecified dose in patients with acute decompensated heart failure compared to placebo when both were added to standard care. Methods: This was a randomised, double-blind, placebo-controlled, multicenter study. After the placement of a Swan–Ganz catheter, 121 patients with acute decompensated heart failure were randomly assigned to double-blind treatment with placebo or rhANP (initiated at a rate of 0.1 µg/kg/min, adjusted to 0.15 ug/kg/min half an hour later if the systolic blood pressure was more than 100 mmHg and the PCWP was 15 mmHg or higher, and stopped one hour later from the initiation). The haemodynamic parameters were measured at 0.25, 0.5, 0.75, 1, 3, 6 and 12 h after the start of study drug. The primary end-point was PCWP at 1 h. Adverse events were monitored through study day 3, and mortality was assessed through a month. Results: 93 patients were randomised to rhANP group and 28 to the placebo group at a ratio of 3:1 using block of size 4. Baseline characteristics were similar among patients in the study groups, and PCWP were 23.71 ± 7.0 and 25.66 ± 8.78 mmHg in rhANP and placebo group, respectively (p = 0.226). The mean reduction in PCWP was greater with rhANP (−5.45 mmHg) than placebo (-2.03 mmHg) at 30 min, and there was significant difference for the mean PCWP between groups (p = 0.002). The maximum decrease of PCWP in rhANP group was observed at 1 h (−7.74 vs −1.82 mmHg with placebo), and the mean PCWP of the two groups were significantly different (p < 0.001). At 3 h, PWCP was sustainedly lower in rhANP group (19.52 ± 6.55 mmHg) than in placebo group (24.79 ± 8.42 mmHg) (p < 0.001). However, no significant differences were found between the two groups for PCWP at 6 h (21.43 ± 6.51 and 24.79 ± 10.64 mmHg, p = 0.125). The rate of hypotension and other adverse event were even in the two groups (p = 0.111). Conclusions: The short-term infusion of rhANP has prompt haemodynamic improvement in patients with acute decompensated heart failure compared to placebo added to standard care.